Implementasi Enterprise Resource Planning Berbasis Odoo untuk Meningkatkan Efisiensi Operasional Menggunakan Analisis Deskriptif Komparatif - Salma, Aulia Happy; Latif, Muhammad Azka; Afriza, Mohammad Maulana; Rizqiyanto, Nanda Lutfi; Supriyono, Supriyono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid advancement of information technology requires companies, including Micro, Small, and Medium Enterprises (MSMEs), to manage their business processes in an integrated manner to enhance operational efficiency, improve data processing accuracy, and enhance the quality of managerial decision-making. The utilisation of integrated information systems has become a crucial factor in supporting the sustainability and competitiveness of MSMEs amid an increasingly complex business environment. CV Anak Rimba, a manufacturing company engaged in the production of processed food products, continues to face various operational challenges, particularly due to the implementation of manual and fragmented data recording systems across departments. These conditions result in inaccuracies in calculating the Cost of Goods Manufactured (COGM), inconsistencies in raw material and finished goods inventory data, and delays in the preparation of financial reports required by management. Therefore, this study aims to implement an Enterprise Resource Planning (ERP) system based on Odoo as a solution to integrate production processes, inventory management, and financial recording in a unified system. The research method employed is a case study with a comparative descriptive analysis approach, utilising system simulation with dummy data. The configured modules include Manufacturing, Inventory, Purchase, Sales, and Accounting. The results indicate that the implementation of an Odoo-based ERP is able to automate transaction recording, calculate COGM in real-time, synchronise inventory data, and generate accurate and timely financial reports. Thus, the implementation of an Odoo-based ERP system is proven to be effective in improving operational efficiency and data transparency at CV Anak Rimba.